2021
DOI: 10.1029/2020ja028091
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Intensity Patterns of OH(6,2) and O(1S) Airglow Driven by Long‐Period Waves Observed Over the Andes Lidar Observatory

Abstract: Simultaneous OH(6,2) and O(1S) nightglow measurements obtained at the Andes Lidar Observatory (ALO) (30.3°S, 70.7°W) from September 2011 to April 2018 have been analyzed to investigate an unusual intensity pattern, that is, O(1S) nightglow intensity enhancement concurrent with OH(6,2) nightglow intensity weakening. We identified 142 nights showing that behavior during the ∼6.5‐year period. The data set comprised of these 142 nights displayed a semiannual occurrence rate with maxima during the equinoxes. A semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Researchers at Andes Lidar Observatory report 142 nights from September 2011 to April 2018 have an unusual patten of O( 1 S) night airglow enhancement with concurrent weaker OH(6,2) emission. This data set showed a semi-annual occurrence rate reaching maxima near the equinoxes 20 . Thirty years of airglow data at OI 557.7 nm and OI 630.0 nm have been used to establish a data driven model consistent with the GLOW airglow model.…”
Section: Introductionmentioning
confidence: 86%
“…Researchers at Andes Lidar Observatory report 142 nights from September 2011 to April 2018 have an unusual patten of O( 1 S) night airglow enhancement with concurrent weaker OH(6,2) emission. This data set showed a semi-annual occurrence rate reaching maxima near the equinoxes 20 . Thirty years of airglow data at OI 557.7 nm and OI 630.0 nm have been used to establish a data driven model consistent with the GLOW airglow model.…”
Section: Introductionmentioning
confidence: 86%
“…Here again, since it is the same region of the Galactic plane (Puppis and Pyxis) that goes through the zenith and since the ecliptic if far from zenith for all these measures, the most plausible explanation is that the contribution of the airglow to the sky brightness is increasing from the southern hemisphere summer solstice to the autumn equinox. The hypothesis that the airglow constitutes an important contribution to the zenithal sky brightness depending on the period of the year is supported by Liu et al 30 and Amaro-Rivera et al 31 where it is reported that the airglow strongest emission rate takes place at the end of April and beginning of May in the southern hemisphere according to both an annual and a semi-annual cycles. Nighttime O( S) emission of the airglow with a green line at 557 nm dominates the OH emission and matches the Unihedron SQM maximum spectral response which is used in the Ninox system.…”
Section: Influence Of Natural Light Sourcesmentioning
confidence: 88%
“…Amaro‐Rivera et al. (2021) have presented a detailed analysis showing the dominance of tidal modes over ALO using airglow images and numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely the product of the wind shear in the lower thermosphere, causing convergence of electrons to a thin region under the influence of the Earth's magnetic field. The sporadic E layer then descends due to a downward drift of the plasma under the influence of the diurnal tide dominant over ALO latitude (Amaro‐Rivera et al., 2021). At altitudes <100 km, the Na + ions in the E s layer recombine with free electrons producing neutral Na that would be detected by the Lidar system as a sporadic sodium layer (Na s ) (e.g., Raizada et al., 2015).…”
Section: Discussionmentioning
confidence: 99%